PELATIHAN BUDIDAYA TANAMAN JERUK BEBAS PENYAKIT CVPD DI DESA KERTA GIANYAR - Adiartayasa, W.; Wijaya, I.N.; Wirawan, I. G.P.; Darmiati, N.N.; Siadi, I K. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
CVPD disease (citrus vein phloem degeneration) is an important disease of citrus. Diseases spread by seeds of citrus plants that have been infected CVPD and is transmitted by insect vectors D. citri. Citrus plants are attacked CVPD show symptoms of leaf yellowing or chlorosis, leaf bones remain green color, leaf size becomes smaller and the leaves become thick and stiff. The observation of plant morphology in Kintamani obtained 10 types of citrus are orange Siam, Selayar, Besakih, Tejakula, Seponten, Nipis, Purut, Limo, and Pomelo. Symptoms of the disease CVPD on each type of citrus plants with symptoms of chlorosis varied. The training aims to increase knowledge of disease-free citrus cultivation CVPD. This training has been implemented in Kerta Village Office, on Wednesday, August 10, 2016. This event was attended by 20 farmers and five lecturers from the Faculty of Agriculture, Udayana University. The evaluation results were obtained 15 people in charge of 90 percent of the material, and 5 of the people control 60 percent of the material. Farmers expect their ongoing training and guidance on cultivation of citrus.